Analisis Monday Effect Dan Weekend Effect Di Sektor Energi Di Bursa Saham Indonesia Pada Tahun 2021-2025 - Salma Nur Rahma Dany; Tri Rachmat Rizki (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research is a comparative quantitative approach. This study aimed to analyze the Monday effect and weekend effect in the energy sector for energy sector companies. The population in this study were energy sector companies listed on the Indonesia Stock Exchange (IDX) The population in this study consisted of 16 energy sector companies listed on the IDX in 2021-2024. This study used purposive sampling, a sampling technique in which samples are selected based on certain criteria or considerations relevant to the research objectives, rather than randomly. The results of the study indicate a Monday effect in energy sector companies during the 2021-2024 period and a weekend effect in energy sector companies during the 2021-2024 period. The weekend effect was identified by the emergence of a significant positive return pattern on Mondays compared to other days.